Managing the boundaries of collaborative research: a contribution from cultural theory. (1st January 1999) - Turpin, Tim
Research collaboration across university and industry boundaries has increased rapidly during the past decade. Consequently, research inputs and outputs are far more collective than in the past. A critical issue for both universities and industrial enterprises is to manage the cultural interaction between the two sectors in a way that maintains the inherent strengths of the research contribution made by both sides of collaborative arrangements. This requires the development of structures and processes conducive to maintaining organisational diversity yet capable of building long-term structural compatibility. Cultural theory offers some analytical perspectives that can assist in formulating organisational structures for managing university and industry collaborative research. It does this by offering a framework for understanding the relationship between organisational structures and control and the cultural values embedded in the perspectives and views of academic researchers.